Value-Based Crisis Management in Islamic Boarding School: A Model for Restoring Public Trust and Institutional Resilience - Fitri, Nadya; Kiram, Syaiful; Junaedi, Erik; Firdaus, Hanif (QUALITY, 2026)
Research in crisis management has predominantly focused on corporate and secular organizations, providing a limited understanding of how Islamic educational institutions manage crises and restore public trust. This study examines crisis typologies, crisis management strategies, and the role of religious values in crisis governance at Pondok Pesantren Darul Amin in Southeast Aceh. A qualitative case study approach was employed, with data collected through in-depth interviews with pesantren leaders, teachers, parents, and complemented by document analysis. The findings reveal three interconnected crisis typologies: internal crises that escalate into the public sphere; perception-based crises that are amplified through digital media; and structural crises that arise from changing societal expectations. Crisis responses are implemented through transparent communication, corrective actions, institutional learning, and the integration of the values of amanah, taqwa, ikhlas, and ukhuwah. This study proposes a Value-Based Crisis Management Model, demonstrating that religious values can function as strategic governance mechanisms that shape crisis responses, trust restoration, and institutional resilience. This extends the scope of conventional, communication-centered crisis management frameworks.